Intensive Therapy of Patients with Acetic Acid Poisoning Complicated by Shock - A. A. Stopnitsky; R. N. Akalaev (Общая реаниматология, 2014)
Objective: to evaluate the efficiency of the elaborated intensive therapy policy for acute acetic acid poisoning complicated by exotoxic shock.Subjects and methods. The results of treatment were analyzed in 72 patients admitted in 2008—2012 with severe acute acetic acid poisoning complicated by exotoxic shock. The patients were divided into 2 groups: 1) combination therapy added by an improved intensive therapy complex; 2) conventional therapy. All the patients underwent comprehensive clinical and laboratory examination.Results and discussion. Group 1 versus the study group showed 1.7-, 2.0-, and 2.4- fold increases in the reduction of free hemoglobin levels 12, 24, and 48 hours after applying the improved complex of intensive  therapy,  respectively.  In  Group  1,  hemodynamic  and  acidbase  balance  parameters  recovered  much  faster  and  the incidence  of  acute  renal  failure  and  mortality  rates  were  2.1  and  2.0  times  lower  than  those  in  the  comparison  group.Conclusion. Incorporation of the agents that correct volemic disorders and improve microcirculation into intensive therapy for acute acetic acid poisoning can considerably reduce the time of shock emergence, prevent acute renal failure, and decrease mortality rates.